2018
DOI: 10.1371/journal.pone.0207032
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic approach for assessing cancer risk due to benzo[a]pyrene in barbecued meat: Informing advice for population groups

Abstract: BackgroundConsumption of meat prepared by barbecuing is associated with risk of cancer due to formation of carcinogenic compounds including benzo[a]pyrene (BaP). Assessment of a population’s risk of disease and people’s individual probability of disease given specific consumer attributes may direct food safety strategies to where impact on public health is largest. The aim of this study was to propose a model that estimates the risk of cancer caused by exposure to BaP from barbecued meat in Denmark, and to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…The elimination potential on BPA in male was higher than that in female; Inversely, the elimination potential on BaP in female was higher than that in male. Interestingly, the level of dimethoate and BaP in male was significantly higher than that in female before exercise which may suggested that different lifestyle like smoking and eating barbecued food could contribute to the accumulation of BaP [41,42]. Different exercises seem to have various elimination potential on environmental pollutants in the present study.…”
Section: Discussionmentioning
confidence: 51%
“…The elimination potential on BPA in male was higher than that in female; Inversely, the elimination potential on BaP in female was higher than that in male. Interestingly, the level of dimethoate and BaP in male was significantly higher than that in female before exercise which may suggested that different lifestyle like smoking and eating barbecued food could contribute to the accumulation of BaP [41,42]. Different exercises seem to have various elimination potential on environmental pollutants in the present study.…”
Section: Discussionmentioning
confidence: 51%
“…Esse fator pode estar relacionado ao nível de conhecimento do paciente sobre a doença. Surpreendentemente, ao contrário da literatura existente, idade não foi associada a pior conhecimento das indicações de medicamentos (Jakobsen et al, 2018;Vozoris et al, 2019;Laforgue et al, 2020).…”
Section: Perfil Socioeconômicounclassified
“…For Danish consumers who frequently barbecue an estimate of barbecuing 30 times per year only corresponds to every day during a summer holiday and does not take into account the all-year popularity of barbecuing. A probabilistic approach assessing the cancer risk due to BaP in barbecued meat concluded that for the Danish population barbecuing would result in one to approximately 4100 new cancer cases over a lifetime (Jakobsen et al 2018). The breadth of the range reflects the broad uncertainty of the estimate.…”
Section: Difficulties In Assessing Pah Exposure From Barbecuingmentioning
confidence: 99%